Trigeminal neuropathy with nasal ulceration: report of two cases and one necropsy. Issue 2 (February 1976) - Spillane, J D; Urich, H
Abstract : Two cases are reported of progressive trigeminal neutopathy with nasal ulceration. One patient developed signs of spinal cord involvement 15 years after the onset of trigeminal symptoms and died after a total course of 21 years. Necropsy revealed an unusual trigeminospinal system degeneration with deposition of amyloid-like substances in the affected structures. The other patient is alive eight years after the onset of symptoms, the only indication of a lesion outside the trigeminal nerve being a patch of numbness in one leg.